Pengembangan Bahan Ajar Materi Perbandingan Bercirikan Realistic Mathematics Education - Manopo Manopo; Sudirman Sudirman; I Made Sulandra (Pascasarjana Universitas Negeri Malang, 2018)
Abstract: The aim of this research is to delevop a proportion textbook characterized Realistic Mathematics Education (RME) which the criteria are valid, practical, and effective. The textbook is developed by plomp model which has three stages; preliminary research, prototyping, assessment. Validation result shows the textbook satisfying valid criteria (81,25). Based on result of development study in MTs Almaarif 01 Singosari, the texbook satisfies practical criteria. All of activites both teacher and student succeed (100), even though there are some weaknesses and student' questionnaire show students response indicating are very positive (98,33) toward the textbook. The textbook  satisfies effective criteria, although 62% had reached KKM, 35% students got score    84 in comprehensive textbook test. Teacher is recommended to take attention on every activities in order to make all of student get engaged actively in learning. Abstrak: Penelitian ini bertujuan untuk mengembangkan bahan ajar materi perbandingan bercirikan Realistic Mathematics Education (RME) dengan kriteria valid, praktis, dan efektif. Bahan ajar ini dikembangkan dengan model Plomp yang memiliki tiga tahap pengembangan yaitu tahap pendahuluan, prototipe dan asesmen. Hasil validasi menunjukkan bahan ajar yang dikembangkan memenuhi kriteria valid (81,25). Berdasarkan hasil uji coba lapangan di MTs Almaarif 01 Singosasi, bahan ajar memenuhi kriteria praktis. Semua kegiatan guru dan siswa terlaksana (100), walaupun masih ada kekurangan dan hasil angket respon siswa menunjukkan respon siswa sangat positif (98,33) terhadap bahan ajar. Bahan ajar memenuhi kriteria efektif, walaupun 62% siswa mencapai nilai KKM namun 35% siswa memperoleh nilai  84 pada tes penguasaan bahan ajar. Guru disarankan untuk memerhatikan setiap kegiatan agar semua siswa terlibat aktif dalam pembelajaran.